Pengaruh Brand Image dan Brand Awareness Terhadap Keputusan Pembelian Produk Sariayu Martha Tilaar di Kota Surabaya - Ariq Satria Supangkat; Hery Pudjoprastyono (UNHI Press, 2022)
This study aims to identify how the influence of brand image and brand awareness on the purchasing decisions of Sariayu Martha Tilaar products in the city of Surabaya. This research method is quantitative by taking a sample of 50 respondents and distributing questionnaires in the city of Surabaya with the help of Google Forms. The sampling technique used was non-probability sampling with the purposive sampling method. The sample consists of respondents who live around the city of Surabaya, aged 17 years and over, and buyers of Sariayu Martha Tilaar products. The data taken from the respondents are primary data and secondary data. The analysis technique used in this study uses Partial Least Square (PLS) with validity testing, reliability testing, and hypothesis testing. Based on the data from this study, it can be concluded that the purchasing decision of Sariayu Martha Tilaar Cosmetics or Skin Care products is positively and significantly influenced by the variables of brand image and brand awareness.